2016
DOI: 10.1007/s10120-016-0651-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of early gastric cancer patients after noncurative endoscopic submucosal dissection in a large consecutive patient series

Abstract: Background Clinical outcomes of early gastric cancer (EGC) patients after noncurative endoscopic submucosal dissection (ESD) have not been fully elucidated; we therefore aimed to clarify these outcomes. Methods A total of 3058 consecutive patients with 3474 clinically diagnosed EGCs at initial onset underwent ESD with curative intent at our hospital between 1999 and 2010. We retrospectively assessed the following clinical outcomes of noncurative gastric ESD patients with a possible risk of lymph node (LN) meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
97
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 35 publications
4
97
2
Order By: Relevance
“…With a curative operation, a greater than 96% 5-year survival rate can be achieved in EGC with lymph node metastasis at stages such as T1N1 [25]. Even after noncurative endoscopic resection of EGC, additional radical gastrectomy with lymph node dissection showed a 5-year overall AGC advanced gastric cancer, CR curative resection, CTx chemotherapy, EGC early gastric cancer, LN lymph node, NCR noncurative resection, STG subtotal gastrectomy, TG total gastrectomy Pattern of extragastric recurrence and the role of abdominal computed tomography in… 849 survival rate of 94.3-94.7%, which is significantly greater (by about 10 percentage points) than that seen after no treatment [26][27][28]. For extragastric recurrences involving only regional lymph nodes, some case reports and studies showed good prognosis after curative surgery [8,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a curative operation, a greater than 96% 5-year survival rate can be achieved in EGC with lymph node metastasis at stages such as T1N1 [25]. Even after noncurative endoscopic resection of EGC, additional radical gastrectomy with lymph node dissection showed a 5-year overall AGC advanced gastric cancer, CR curative resection, CTx chemotherapy, EGC early gastric cancer, LN lymph node, NCR noncurative resection, STG subtotal gastrectomy, TG total gastrectomy Pattern of extragastric recurrence and the role of abdominal computed tomography in… 849 survival rate of 94.3-94.7%, which is significantly greater (by about 10 percentage points) than that seen after no treatment [26][27][28]. For extragastric recurrences involving only regional lymph nodes, some case reports and studies showed good prognosis after curative surgery [8,19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from Korea and Japan included large populations of EGC patients and longer follow-up periods [8,9,19,28]. In terms of extragastric recurrence, all of the studies to date have reported a low incidence and a common pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Additional gastrectomy should be performed particularly in noncurative gastric ESD patients with lymphovascular invasion even in the elderly cohort without comorbidities (4,5). Nevertheless, we have not had enough data to support the real feasibility of gastric ESD linked to the survival benefits for elderly patients with comorbidities.…”
mentioning
confidence: 99%
“…It is possible that lymphatic invasion and subsequent LNM may be a primary route for recurrence in non-curative ESD in the simple followup patients. And, lymphovascular invasion was identified as an independent predictor of gastric cancer-related death in non-curative gastric ESD patients in the simple followup group (4,5). Additional surgical intervention could be determined based on a comprehensive review of the resected specimen including lymphovascular tumor emboli, tumor size, histological type and depth of invasion.…”
mentioning
confidence: 99%
See 1 more Smart Citation